Treatment response assessment of breast masses on dynamic contrast-enhanced magnetic resonance scans using fuzzy c -means clustering and level set segmentation - Shi, Jiazheng; Sahiner, Berkman; Chan, Heang-Ping; Paramagul, Chintana; Hadjiiski, Lubomir M.; Helvie, Mark; Chenevert, Thomas (Medical physics (Lancaster), 2009)
The goal of this study was to develop an automated method to segment breast masses on dynamic contrast-enhanced (DCE) magnetic resonance (MR) scans and to evaluate its potential for estimating tumor volume on pre- and postchemotherapy images and tumor change in response to treatment. A radiologist experienced in interpreting breast MR scans defined a cuboid volume of interest (VOI) enclosing the mass in the MR volume at one time point within the sequence of DCE-MR scans. The corresponding VOIs over the entire time sequence were then automatically extracted. A new 3D VOI representing the local pharmacokinetic activities in the VOI was generated from the 4D VOI sequence by summarizing the temporal intensity enhancement curve of each voxel with its standard deviation. The method then used the fuzzy c -means (FCM) clustering algorithm followed by morphological filtering for initial mass segmentation. The initial segmentation was refined by the 3D level set (LS) method. The velocity field of the LS method was formulated in terms of the mean curvature which guaranteed the smoothness of the surface, the Sobel edge information which attracted the zero LS to the desired mass margin, and the FCM membership function which improved segmentation accuracy. The method was evaluated on 50 DCE-MR scans of 25 patients who underwent neoadjuvant chemotherapy. Each patient had pre- and postchemotherapy DCE-MR scans on a 1.5 T magnet. The in-plane pixel size ranged from 0.546 to 0.703 mm and the slice thickness ranged from 2.5 to 4.5 mm. The flip angle was 15°, repetition time ranged from 5.98 to 6.7 ms, and echo time ranged from 1.2 to 1.3 ms. Computer segmentation was applied to the coronal T1-weighted images. For comparison, the same radiologist who marked the VOI also manually segmented the mass on each slice. The performance of the automated method was quantified using an overlap measure, defined as the ratio of the intersection of the computer and the manual segmentation volumes to the manual segmentation volume. Pre- and postchemotherapy masses had overlap measures of 0.81 ± 0.13 ( mean ± s .d . ) and 0.71 ± 0.22 , respectively. The percentage volume reduction (PVR) estimated by computer and the radiologist were 55.5 ± 43.0 % ( mean ± s .d . ) and 57.8 ± 51.3 % , respectively. Paired Student’s t test indicated that the difference between the mean PVRs estimated by computer and the radiologist did not reach statistical significance ( p = 0.641 ) . The automated mass segmentation method may have the potential to assist physicians in monitoring volume change in breast masses in response to treatment.